Macroeconomic and Bank-Specific Determinants of Non-Performing Loans: Evidence from Nepalese Banking System - Laxmi Koju; Ram Koju; Shouyang Wang (Journal of Central Banking Theory and Practice, 2018)
This paper aims to evaluate the macroeconomic and bank-specific determinants of non-performing loans (NPL) in the Nepalese banking system using both static and dynamic panel estimation approaches. The study considers 30 Nepalese commercial banks over the period 2003-2015 and uses 7 bank-specific and 5 macroeconomic variables to assess the impact of banking management and economic indicators on NPL. The findings show that NPLs have significant positive relationship with the export to import ratio, inefficiency, and assets size and a negative relationship with the GDP growth rate, capital adequacy, and inflation rate. The results of the empirical study indicate low economic growth as the primary cause of high NPLs in Nepal and suggest that efficient management and effective financial policies are required for a stable financial system and economy. This is the first complete study in the Nepalese banking system and also the first study that has evaluated the effects of remittance, public debts and interest spreads on NPL. The findings of this study will be helpful in designing the macroprudential and fiscal policies in Nepal.
Keywords: E44; G21; 330; economic condition; financial stability; generalized method of moments; monetary policy; non-performing loans; static panel estimation.